LAND PROCUREMENT FOR PUBLIC INTEREST IN LOCAL GOVERNMENTS WITH SMALL SCALE - Arifin, Miftah; Sukrisno, Wijayono Hadi; Arifin, Zaenal (JURNAL USM LAW REVIEW, 2021)
This study has purposes to find out how the mechanism of land procurement for the public interest in local governments, find out the obstacles and solve the problem of land procurement for the public interest on a small scale. Land procurement by the local government sometimes always collides with the stages of land procurement which is a very long process, but the land is needed immediately to support development. Small-scale land procurement is carried out on an area of no more than 5 hectares. Land procurement on a small scale for the public interest can be carried out without going through the determination of the location. The legal consequences are not being able to deposit compensation in court. This study uses a sociological juridical method, namely the discussion based on the provisions of the legislation. The results of this study are that the mechanism for land procurement for the public interest is carried out with accurate research and socialization so that the community understands the positive impact of development for the public interest and counseling so that the community understands the benefits of the project and participates in the success of project development for the public interest. Another obstacle in the implementation of land procurement is the existence of incomplete land ownership data or documents or no land ownership rights, the bureaucracy that guarantees legal certainty that the settlement of these obstacles is carried out with the active role of agencies that require land.